2020
DOI: 10.1007/s00277-020-04194-0
|View full text |Cite
|
Sign up to set email alerts
|

Cooperating, congenital neutropenia–associated Csf3r and Runx1 mutations activate pro-inflammatory signaling and inhibit myeloid differentiation of mouse HSPCs

Abstract: Patients with the pre-leukemia bone marrow failure syndrome called severe congenital neutropenia (CN) have an approximately 15% risk of developing acute myeloid leukemia (AML; called here CN/AML). Most CN/AML patients co-acquire CSF3R and RUNX1 mutations, which play cooperative roles in the development of AML. To establish an in vitro model of leukemogenesis, we utilized bone marrow lin− cells from transgenic C57BL/6-d715 Csf3r mice expressing a CN patient–mimicking truncated CSF3R mutation. We transduced thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…28,29 Cells with RUNX1 and CSF3R mutants exhibited the hyperactivation of inflammatory and immune signaling pathways, involving in the development of LAML. 30 CXCL9 may play a protective role in pulmonary fibrosis through abrogating the EMT induced by anti-inflammation factor TGF-β1. 31 Moreover, tumor-infiltrating lymphocyte-based therapeutic strategies also improve the clinical management of cancer patients, providing a remarkable perspective in tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Cells with RUNX1 and CSF3R mutants exhibited the hyperactivation of inflammatory and immune signaling pathways, involving in the development of LAML. 30 CXCL9 may play a protective role in pulmonary fibrosis through abrogating the EMT induced by anti-inflammation factor TGF-β1. 31 Moreover, tumor-infiltrating lymphocyte-based therapeutic strategies also improve the clinical management of cancer patients, providing a remarkable perspective in tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing studies have shown that tumor immune microenvironment is related to a variety of clinical biological functions in cancers, affecting cancer pathogenesis and the therapeutic response 28,29 . Cells with RUNX1 and CSF3R mutants exhibited the hyperactivation of inflammatory and immune signaling pathways, involving in the development of LAML 30 . CXCL9 may play a protective role in pulmonary fibrosis through abrogating the EMT induced by anti‐inflammation factor TGF‐β1 31 .…”
Section: Discussionmentioning
confidence: 99%